Islamic terrorism in Indonesia: Addressing Government Strategies and Muslim Population - Kustana, Tatan (The Republic of Indonesia Defense University, 2017)
This paper shows how Terrorism has been emerging in the world, the potency to be spread out in the South-East Asian nations, and how Indonesia could face internal challenges to do counter-terrorism of the false Jihad, with multitrack diplomacy, primarily with Police and National Agency for Combating Terrorism counter-terrorism programs. In the perspective of defense strategy, the issue of terrorism brings several implications (Indonesian White Paper 2008, p. 9). The condition of Indonesian community with low educational levels and low economic income becomes target for terrorist actors to expand the network by developing and recruiting new members. The threat of Islamic terrorism is categorized as a national security threat. The Indonesian Government through its security apparatus still have to work hard to hunt down other terrorists, to undertake preventive efforts to prevent Islamic fundamentalist beliefs not to develop and increased education level and the understanding of Islam more comprehensively.